ANALISIS KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN JASA LAYANAN INTERNET - Mr Sewaka (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Technological advances have forced telecommunications companies to increase their competitiveness, despite having to pay a lot of costs. This research was conducted to examine the consumer's decision to use internet services. The scientific approach used is quantitative with a simple random sample technique. While the analysis tool uses multiple linear regression. PT. Dwi Tunggal Putra was chosen as the object of research with 100 users in Jakarta. The results showed that promotion affects consumer psychology. Whereas service influences consumer's feelings. In other words, purchasing decisions are very dependent on the state of consumer psychology, and promotion and service quality has been proven to influence it